2020
DOI: 10.1016/j.scijus.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A cultural change to enable improved decision-making in forensic science: A six phased approach

Abstract: There has been an increased engagement by researchers in understanding the decision-making processes that occur within forensic science. There is a rapidly growing evidence base underpinning our understanding of decision-making and human factors and this body of work is the foundation for achieving truly improved decision-making in forensic science. Such an endeavour is necessary to minimise the misinterpretation of scientific evidence and maximise the effectiveness of crime reconstruction approaches and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 98 publications
0
18
0
1
Order By: Relevance
“…Future research should also explore whether explicit diagnosticity training can further improve forensic examiners' knowledge of domain-specific diagnostic features. Given emerging calls for forensic science training to include human factors research (Earwaker, Nakhaeizadeh, Smit, & Morgan, 2019), it is possible that a brief training intervention could be used to improve examiners' real-world visual comparison performance.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should also explore whether explicit diagnosticity training can further improve forensic examiners' knowledge of domain-specific diagnostic features. Given emerging calls for forensic science training to include human factors research (Earwaker, Nakhaeizadeh, Smit, & Morgan, 2019), it is possible that a brief training intervention could be used to improve examiners' real-world visual comparison performance.…”
Section: Discussionmentioning
confidence: 99%
“…Very simply put, an error is when an incorrect decision is made given the information available. However, there are many complex issues to address in determining what counts as an error and the use of the term error (37), which underpins establishing error rates. To start, are all errors equal?…”
Section: Why Are Error Rates So Elusivementioning
confidence: 99%
“…Whilst a physical presence at the scene enables students to consider in practice aspects of contamination avoidance, scene control, and evidence recovery methods, often these activities can, perhaps, be a barrier to the more interpretative aspects of crime scene investigation. Through separating the physical application of practical techniques with the more holistic consideration of a crime scene through a virtual approach, it becomes possible to focus the students on aspects of decision making and rationale for activities at the scene, stressing the importance of the interpretative aspects throughout the forensic process, as is key to instill in the next generation of practitioners [ 21 ]. Yet all of this good work needs to be considered in the context of recent research that has shown that 71% of students would struggle with motivation to learn and 63% would feel less prepared to take assignments and assessments with limited face-to-face teaching [ 23 ].…”
Section: Moving Forwardmentioning
confidence: 99%